Caribbean Bananas : The Macroeconomic Impact of Trade Preference Erosion - Cashin, Paul (IMF Working Papers; Working Paper, 2010)
This paper examines the macroeconomic effects of the erosion of trade preferences, with a focus on the export of Caribbean bananas to Europe. Estimates are made of the magnitude of implicit assistance provided over a period of three decades to eastern Caribbean countries through banana trade preferences. The value of such assistance rose until the early 1990s, and has declined precipitously since then. Using vector autoregressive analysis, the paper finds that changes in the level of implicit assistance have had a considerable macroeconomic impact, especially on Caribbean real GDP growth.